Soybean Nodulation Response to Cropping Interval and Inoculation in European Cropping Systems - Halwani, Mosab; Reckling, Moritz; Egamberdieva, Dilfuza; Omari, Richard Ansong; Bellingrath-Kimura, Sonoko D.; Bachinger, Johann; Bloch, Ralf (Frontiers in Plant Science, 2021)
To support the adaption of soybean [Glycine max (L) Merrill] cultivation across central Europe, the availability of compatible soybean-nodulating Bradyrhizobia (SNB) is essential. Little is known about the symbiotic potential of indigenous SNB in central Europe and the interaction with SNB inoculum from commercial products. The objective of this study was to quantify the capacity of indigenous and inoculated SNB strains on the symbiotic performance of soybean in a pot experiment using soils with and without soybean history. Under controlled conditions in a growth chamber, the study focused on two main factors: soybean cropping interval (time since the last soybean cultivation; SCI) and inoculation with commercial Bradyrhizobia strains. Comparing the two types of soil, without soybean history and with 1-4 years SCI, we found that plants grown in soil with soybean history and without inoculation had significantly more root nodules and higher nitrogen content in the plant tissue. These parameters, along with the leghemoglobin content were found to be variable among soils with 1-4 years SCI and did not show a trend over the years. The soil without soybean history and with inoculation showed a significant increase in nodulation rate, leghemoglobin content, and soybean tissue nitrogen concentration. The study found that response to inoculation varied significantly as per locations in soil with previous soybean cultivation history. Inoculated soybean grown on loamy sandy soils from the location Müncheberg had significantly more nodules as well as higher green tissue nitrogen concentration compared to non-inoculated plants. No significant improvement in nodulation rate and tissue nitrogen concentration was observed for inoculated soybean grown on loamy sandy soils from the location Fehrow. These results suggest that introduced SNB strains remained viable in the soil and were still symbiotically competent for up to 4 years after soybean cultivation. However, the symbiotic performance of the SNB remaining in the soils was not sufﬁcient in all cases and makes inoculation with commercial products necessary. The SNB strains found in the soil of central Europe could also be promising candidates for the development of inoculants and already represent a contribution towards the successful cultivation of soybean in central Europe.